2018
DOI: 10.3892/ijmm.2018.3409
|View full text |Cite
|
Sign up to set email alerts
|

Schizandrin B inhibits the cis‑DDP‑induced apoptosis of HK‑2 cells by activating ERK/NF‑κB signaling to regulate the expression of survivin

Abstract: The nephrotoxicity of cisplatin limits its clinical application. Schizandrin B (SchB) has been demonstrated to have a variety of potential cytoprotective activities. The present study explored the molecular mechanisms by which SchB inhibits the dichlorodiammine platinum (DDP)-induced apoptosis of HK-2 proximal tubule epithelial cells. In vitro assays demonstrated that SchB increased the viability of HK-2 cells, alleviated the cis-DDP-induced activation of caspase-3, reduced apoptosis and improved the nuclear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…It has been extensively utilized to cure different types of neoplasms, including head and neck ( 9 , 10 ), lung ( 11 , 12 ), ovarian ( 13 , 14 ), breast ( 15 , 16 ), brain ( 17 , 18 ), kidney ( 19 , 20 ), and esophagus cancers ( 21 23 ). In general, DDP and other platinum-based compounds are considered to be cytotoxic drugs, which can induce apoptosis of cancer cells ( 24 ). Numerous molecular anticancer mechanisms have been described, including the induction of p53 signaling and cell cycle arrest ( 25 , 26 ), downregulation of proto-oncogenes and anti-apoptotic proteins, and activation of both intrinsic and extrinsic apoptosis ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been extensively utilized to cure different types of neoplasms, including head and neck ( 9 , 10 ), lung ( 11 , 12 ), ovarian ( 13 , 14 ), breast ( 15 , 16 ), brain ( 17 , 18 ), kidney ( 19 , 20 ), and esophagus cancers ( 21 23 ). In general, DDP and other platinum-based compounds are considered to be cytotoxic drugs, which can induce apoptosis of cancer cells ( 24 ). Numerous molecular anticancer mechanisms have been described, including the induction of p53 signaling and cell cycle arrest ( 25 , 26 ), downregulation of proto-oncogenes and anti-apoptotic proteins, and activation of both intrinsic and extrinsic apoptosis ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Natural products types Representative natural products [120,121]. It is believed that Schisandra sphenanthera extract facilitates the nuclear accumulation of the transcription factor NRF2 to mitigate cisplatin-induced nephrotoxicity, which is important for therapeutic approaches to AKI [122].…”
Section: Mechanismsmentioning
confidence: 99%
“…For instance, Ran et al evaluated that Sch B alleviated osteoarthritis by repressing NF-κB and MAPK pathways ( Ran et al, 2018 ). Liu et al (2018) explained that dichlorodiammine platinum (DDP) promoted cell apoptosis, whereas Sch B repressed this effect by regulating ERK/NF-κB pathway. Our data showed that Sch B exposure downregulated the expression of PI3K/AKT pathway-related proteins (p-PI3K and p-AKT), which meant that Sch B regulated osteosarcoma progression by blocking PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%